In Situ Observation of Successive Crystallizations and Metastable Intermediates in the Formation of Metal–Organic Frameworks. (6th January 2016) - Yeung, Hamish H.‐M.; Wu, Yue; Henke, Sebastian; Cheetham, Anthony K.; O'Hare, Dermot; Walton, Richard I.
Abstract: Understanding the driving forces controlling crystallization is essential for the efficient synthesis and design of new materials, particularly metal–organic frameworks (MOFs), where mild solvothermal synthesis often allows access to various phases from the same reagents. Using high‐energy in situ synchrotron X‐ray powder diffraction, we monitor the crystallization of lithium tartrate MOFs, observing the successive crystallization and dissolution of three competing phases in one reaction. By determining rate constants and activation energies, we fully quantify the reaction energy landscape, gaining important predictive power for the choice of reaction conditions. Different reaction rates are explained by the structural relationships between the products and the reactants; larger changes in conformation result in higher activation energies. The methods we demonstrate can easily be applied to other materials, opening the door to a greater understanding of crystallization in general.